2013 15th European Conference on Power Electronics and Applications (EPE) 2013
DOI: 10.1109/epe.2013.6631856
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the passive thermal control system of a lithium-ion battery with heat pipes embedded in an aluminum plate

Abstract: In the design and operation of batteries, effective heat transfer and protection against high operation temperatures are significant issues affecting the lifetime of the battery. This is particularly the case for batteries intended for hybrid machines, where the peak power and current requirements are high. This paper introduces a structure of the thermal protection system for the high-power lithium-ion batteries to be applied to hybrid machines and a methodology for their optimization. The proposed structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[122] and Huang et al [123], several successful attempts also have been made to improve the efficiency and effectiveness of these thermal management systems, generally by integrating and combining different methods and techniques with each other. Nevertheless and as discussed by Xia et al [113] and Murashko et al [120] the application of these technologies found out to be mainly dependent on parameters such as cost, size, compactness, and reliability of the overall system.…”
Section: Discussion and Recommendationmentioning
confidence: 95%
“…[122] and Huang et al [123], several successful attempts also have been made to improve the efficiency and effectiveness of these thermal management systems, generally by integrating and combining different methods and techniques with each other. Nevertheless and as discussed by Xia et al [113] and Murashko et al [120] the application of these technologies found out to be mainly dependent on parameters such as cost, size, compactness, and reliability of the overall system.…”
Section: Discussion and Recommendationmentioning
confidence: 95%
“…• The set S is now the subsequent front, and therefore Cj = S. • This optimizer is superior to previous NSGA ( [5])…”
Section: Description Of Nsga-iimentioning
confidence: 97%
“…Kirill et al [5] presented a thermal protection system design for LIBs used in hybrid machines and a technique for optimizing them. The framework proposed consists of the use of metal plates and heat pipes in the battery cells.…”
Section: Heat Pipe-basedmentioning
confidence: 99%
See 2 more Smart Citations